ANALISIS TAWHIDI STRING RELATIONS PADA KELOMPOK KREATIF TENUN TAPIS DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DESA - ana santika, ana (Universitas Islam Negeri Raden Intan Lampung, 2025)
ABSTRAK Based on Tawhidi String Relation, this study examines how the creative economy of tapis weaving contributes to the achievement of Sustainable Development Goals (SDGs) in villages and how economic development goals in Tawhidi String Relation are related to SDGs in villages. The Tawhidi String Relation (TSR) technique was used in this descriptive qualitative study. This approach employs the shuratic process (interaction, integration, and evolution) as well as cyclical causality to analyze data based on observations in the field. The research findings indicate that the creative economy of tapis weaving in Gunung Megang village plays a significant role in realizing the SDGs of the village. This can be seen from the achievement of nine village SDGs, namely Village SDG 01, Village SDG 05, Village SDG 08, and Village SDG 18, as well as six components of maqashid syariah, each of which is interconnected (circular causation). Furthermore, the correlation between the direction of the Tawhidi String Relation (TSR) economic development goals and the Sustainable Development Goals (SDGs) for villages includes people-oriented and maslahah-oriented approaches. Through the village government of Gunung Megang, the potential of the local village has been maximized, and the quality of human resources has been improved by utilizing village funds to the fullest extent through village contributions and actively supporting community businesses through training programs for small and medium enterprises (SMEs). Kybord: Ekonomi Kreatif, Tenun Tapis, SDGs, Tawhidi String Relation